PENGEMBANGAN MEDIA PEMBELAJARAN PERMAINAN ULAR TANGGA BIOLOGI PADA MATERI KLASIFIKASI MAKHLUK HIDUP KELAS VII - Marhaeni, Marhaeni; Nurmiati, Nurmiati; Ekaningtiyas, Maya (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study was to test the feasibility of developing learning media for the snake and ladder game on the classification of living things. The development is carried out using the ADDIE development model only in three stages, namely analysis, design, and development. Learning media was developed and tested on class VII students of MTs Darussholihin NW Kalijaga. The object of this research is the snake and ladder game learning media and was validated by three validators. Based on the results of validation and testing on students, the average percentage of eligibility is 93%. The results of this study indicate that the learning media developed is suitable to be used as a medium to support the learning process, especially in the material classification of living things.